Genetic diversity and population structure of Glochidion subgenus Phyllanthodendron (Phyllanthaceae) in Thailand and Laos revealed by SCoT markers - ZAHROBATUL LIL ILMI; PRANOM CHANTARANOTHAI; HENRIK BALSLEV; JIDAPA DUANYAI; PIMWADEE PORNPONGRUNGRUENG (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Ilmi ZL, Chantaranothai P, Balslev H, Duanyai J, Pornpongrungrueng P. 2025. Genetic diversity and population structure of Glochidion subgenus Phyllanthodendron (Phyllanthaceae) in Thailand and Laos revealed by SCoT Markers. Biodiversitas 26: 5534-5543. Two species of Glochidion subgenus Phyllanthodendron (Phyllanthaceae) were previously recorded in Thailand and Laos: Glochidion mirabile, which occurs throughout Thailand and adjacent Laos, and Glochidion kaweesakii, which is a local endemic in northeastern Thailand. During field work, we encountered three populations that were difficult to assign to either of the two known species on morphological grounds. In this study, we used SCoT markers to assess genetic diversity and relationships among 101 individuals from 22 populations to clarify their taxonomic status. Seven SCoT primers that provided 100% polymorphic bands (mean Polymorphic Information Content (PIC) = 0.26) were selected for the analysis. We found low genetic variation for G. kaweesakii (Nei's genetic diversity (H) = 0.05), unidentified populations 1 (H = 0.05), and unidentified populations 2 (H = 0.06). Both G. mirabile and the third unidentified population exhibited low genetic variation within populations but high variation between populations, which was associated with a high genetic differentiation coefficient among populations (Gst = 0.67 and 0.66, respectively). Clustering analysis grouped all individuals into three clusters. Cluster I included G. mirabile and the third unidentified population, Cluster II included the two remaining unidentified populations, and Cluster III consisted of G. kaweesakii. Population structure analysis identified two groups that are significantly different from clustering analysis. Genetic relationships were consistent with geographic distribution. The results support the possibility that the third unidentified population should be considered part of G. mirabile, whereas the two remaining unidentified populations represent potentially distinct lineages that require an integrative taxonomic approach to confirm. Given the low genetic diversity and limited gene flow, a comprehensive conservation strategy focusing on improving habitat connectivity and facilitating gene flow should be considered to enhance the long-term viability of these species.